Monitoring Aedes population using ovitrap index and larval abundance in an urban university residence - Emma Aishah A; Muhammad Firdaus MF; Nur Syafiqah T; Rozana MS; Sugasini SL; Syamsa Rizal A; Ahmad Firdaus MS; Aishah Hani Azil (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Autocidal ovitraps have played a significant role in surveillance and control of dengue vectors, Aedes aegypti and Aedes albopictus. Malaysia has witnessed the deployment of several types of autocidal ovitraps, which includes the Mosquito Larvae Trapping Device (MLTD) introduced by Kuala Lumpur City Hall. This study aimed to assess Aedes larval abundance and local meteorological variables in a university residence, in Cheras, Kuala Lumpur. MLTD (n=30) baited with organic NPK fertiliser (5:5:5) solutions were deployed. Larvae collection and trap servicing were performed weekly for a duration of eight weeks. Rearing and species identification for larvae were conducted in the laboratory. Out of 2,152 Aedes larvae, 85% of them were Ae. albopictus whilst the remaining were Ae. aegypti. Outdoor collection of Ae. albopictus surpassed its indoor collection (mean larvae per trap of 9.28 versus 6.08). Conversely, an indoor collection of Ae. aegypti was greater than its outdoor collection (mean larvae per trap of 1.72 versus 0.86). The highest ovitrap indices were observed in Week 5 and 6 which were 90% and 93%, respectively. Week 1 had the lowest ovitrap index, 30%. Our analyses revealed a positive correlation between Aedes larval abundance and maximum temperature (r=0.830, p=0.011) whereas minimum relative humidity was shown to have a negative correlation (r=-0.778, p=0.023), with the larval abundance. Routine monitoring of dengue vectors at its immature stages can provide information on the density and fluctuation of the local mosquito population. Coupled with concurrent meteorological variables, it can guide vector control operations as part of dengue prevention strategies.